1995
DOI: 10.1007/bf00319130
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of neuropeptide Y-like-immunoreactive cells in the gastroenteropancreatic endocrine system of the dogfish

Abstract: This immunocytochemical study was carried out to elucidate the ontogenetic development of neuropeptide Y-like-immunoreactive cells in the gastroenteropancreatic endocrine system of the cloudy dogfish, Scyliorhinus torazame. Immunostained cells first appeared in the pancreas of the embryo at the 15-mm stage, and were also detected in the vitello-intestinal duct of the yolk stalk at the 20-mm stage. These cells were polymorphic, with occasional processes that were sometimes directed toward the vascular wall or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Single endocrine cells are known from the digestive tract of cartilaginous fishes (Cimini et al, 1989;Chiba et al, 1995), Polypterus (Zaccone et al, 1995), lungfishes (Tagliafierro et al, 1996), bowfin Amia calva (Youson et al, 2001), gar Lepisosteus osseus (Groff and Youson, 1997), and several species of teleosts (Tagliafierro, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Single endocrine cells are known from the digestive tract of cartilaginous fishes (Cimini et al, 1989;Chiba et al, 1995), Polypterus (Zaccone et al, 1995), lungfishes (Tagliafierro et al, 1996), bowfin Amia calva (Youson et al, 2001), gar Lepisosteus osseus (Groff and Youson, 1997), and several species of teleosts (Tagliafierro, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…If this is the sequence of differentiation of larval islet tissue then it would be inconsistent with that observed in many other vertebrates, for PP-family peptides are among the last to appear (Berwert et al, 1995). It is important to extend these observations to embryonic intervals in lampreys, for peptides such as NPY have been shown to appear in embryogenesis of the elasmobranch GEP system (Chiba et al, 1995). The youngest larvae to be examined in lampreys (35 days old) already showed insulin-immunoreactive cell clumps in the intestinal epithelium and submucosal area but also in the extrahepatic common bile duct (Youson, 1999).…”
Section: Agnathansmentioning
confidence: 94%
“…The endocrine cells of the gastrointestinal system of elasmobranchs has received a great deal of attention over the years and the reader is referred to several of the early and recent reports (El-Salhy, 1984;Cimini et al, 1989;Tagliafierro et al, 1989;Yui et al, 1990;Chiba et al, 1995;Chiba, 1998). However, despite the many species of elasmobranchs that have been investigated no phylogenetic pattern involving the presence/ absence or distribution of regulatory peptides in the stomach and intestine has emerged.…”
Section: General Morphology Of the Islet Organ In Chondrichthyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the regional distribution and relative frequency of numerous types of regulatory peptides have been demonstrated in the gut of the Pisces. Some endocrine cells in the gut of the various species of bony fish (Rombout and Reinecke, 1984; Rombout et al., 1986; Abad et al., 1987; Jonsson et al., 1987; Elbal et al., 1988; Beorlegui et al., 1992; Kiliaan et al., 1992; Pan and Fang, 1993; Himick and Peter, 1994; Tagliafierro et al., 1996; Andreozzi et al., 1997; Groff and Youson, 1997; Reinecke et al., 1997; Kurokawa et al., 2000), cartilaginous fish (Holmgren and Nilsson, 1983; Faraldi et al., 1988; Tagliafierro et al., 1988; Cimini et al., 1992; Chiba et al., 1995) and cyclostomes (Reinecke, 1987; Cheung et al., 1991; Youson and Potter, 1993) were studied by histochemical, electron microscopical and immunohistochemical methods. In addition, Al‐Mahrouki and Youson (1998) reported that immunohistochemical study of the endocrine cells within the gastro‐entero‐pancreatic system of Osteoglossomorpha, an ancient teleostean group, and they detected some different distribution and frequency of endocrine cells between five species of the Osteoglossomorpha.…”
Section: Introductionmentioning
confidence: 99%